Effects of Water Immersion on the Adhesion between Adhesive Layer and Concrete Block - Jiajun Shi; Yunfeng Pan; Hedong Li; Jun Fu (Advances in Civil Engineering)
The effectiveness of load transfer in the CFRP-adhesive-concrete system highly relies on the integrity of the interfacial bond between adhesive layer and concrete. In the present paper, the effects of water immersion on the mode I fracture energy of the adhesion between CFRP adhesive and concrete were investigated experimentally and numerically. Four-point bending test was conducted to measure the mode I fracture energy of the interfacial layer between adhesive and concrete. The moisture content distribution and the hygrothermal stress were determined by using the finite element method (FEM). The mode I fracture energy was found decreasing with increasing immersion time. The difference between the mode I fracture energy at 2 weeks and 4 weeks is rare. The failure mode of the four-point bending test specimen shifts from concrete failure to interfacial debonding. The moisture content at the adhesive/concrete interface reaches equilibrium after 2 weeks of water immersion. The hygrothermal stress between adhesive and concrete is smaller than the tensile strength of concrete. Deterioration of the physical bond leads to the degradation of bonding strength. The reduction of the mode I fracture energy is more severe than that of the mode II fracture energy.